APPLICATION OF INFORMATION TECHNOLOGY FOR PROMOTION AND SUSTAINABLE MANAGEMENT IN MARINE ECOTOURISM: A CASE STUDY IN BANGSRING, BANYUWANGI - Nurin Hidayati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2016)
Ecotourism is a form of tourism management by promoting the unique tourist attraction such as natural destination, conservation, education and local wisdom. Banyuwangi is a region that makes ecotourism as an important pillar of the economy in coastal areas. Communities in the coastal village of Bangsring District, Banyuwangi, generally have a chance to earn more revenue from ecotourism sector. The existence of coral reefs and beautiful islands are natural potential that can be developed into high-value marine ecotourism, especially with the increase in ecotourism trend. It is also in line with the direction of Government policy in Banyuwangi to advance marine ecotourism sector. Based on information obtained from the chairman of Pokwasmas Samudera Bhakti and KNIH Bangsring, the problem faced by partners related to the development of ecotourism was that Bangsring ecotourism requires more promotions. Information about ecotourism so far has not fully use information technology, whereas characteristics of ecotourism fans who belong to a niche market requires their websites and other social media as an effective media campaign.